2013
DOI: 10.1007/s00248-013-0182-7
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic Serotypes of Vibrio cholerae Isolated from Ships’ Ballast Tanks and Coastal Waters: Assessment of Antibiotic Resistance and Virulence Genes (tcpA and ctxA)

Abstract: There is concern that ships' ballasting operations may disseminate Vibrio cholerae to ports throughout the world. Given evidence that the bacterium is indeed transported by ships, we isolated pandemic serotypes O1 and O139 from ballast tanks and characterized them with respect to antibiotic resistance and virulence genes ctxA and tcpA. We carried out concurrent studies with V. cholerae isolated from coastal waters. Of 284 isolates, 30 were serotype O1 and 59 were serotype O139. These serotypes were overreprese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…E. coli and V. cholerae were quantified at relatively high abundances in the marine biofilm samples, suggesting that biofilms, including those on ships, can be an overlooked reservoir for pathogens (39). Additionally, similar to previous studies on ballast water (8,14,20,21,36,40,41), we have found that both bilge water and boat surface bacterial communities contain a diverse set of organisms related to pathogenic microbes. This finding suggests that bacterial life on boats is not limited to ballast tanks; bacterial communities from the water can exist on any ship, even if it lacks a ballast tank.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…E. coli and V. cholerae were quantified at relatively high abundances in the marine biofilm samples, suggesting that biofilms, including those on ships, can be an overlooked reservoir for pathogens (39). Additionally, similar to previous studies on ballast water (8,14,20,21,36,40,41), we have found that both bilge water and boat surface bacterial communities contain a diverse set of organisms related to pathogenic microbes. This finding suggests that bacterial life on boats is not limited to ballast tanks; bacterial communities from the water can exist on any ship, even if it lacks a ballast tank.…”
Section: Discussionsupporting
confidence: 84%
“…A few studies have looked at the microbial communities of ballast water and in shipping ports. Several studies support the presence of fecal indicator bacteria and pathogens in ballast water and have warned about the transfer of harmful organisms by ships; these studies have been done in Singapore, the Mediterranean Sea, the North Sea, and the Port of Houston (8,21,(35)(36)(37). Other studies have used next-generation sequencing to look at abundances of pathogens in ballast water; these studies have suggested that exchanging ballast water at sea is not effective for removing bacteria from ballast tanks (8,14).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, samples collected in the last 60 years by the continuous plankton recorder (CPR) survey ( Vezzulli et al, 2012 ) showed that the genus Vibrio , including the human pathogen V. cholerae , has increased in prevalence in the last 44 years in the coastal North Sea, and that this increase is correlated with warming SST. Elevated water temperatures might also facilitate the successful invasion of pathogenic variants via food trade ( Nair et al, 2007 ), ballast water ( Dobbs et al, 2013 ), travelers ( Fillion and Mileno, 2015 ) or natural animals. For example, migrating birds may act as vectors of intercontinental transport of V. cholerae ( Vezzulli et al, 2010a ).…”
Section: State Of the Art And Perspectives Of Vibrio mentioning
confidence: 99%
“…Entrained in those discharges are organisms taken up when ballasting and which survived days to months in the tanks. In this way, ballasting operations have introduced nonindigenous organisms globally, and some have subsequently flourished in novel environments and are implicated in deleterious economic, environmental, and public-health issues. , The case for such invasions is much better articulated for invertebrates and harmful algae than for Bacteria, but there is strong evidence that ballast-water discharges introduce fecal-indicator bacteria and bacterial pathogens. …”
Section: Introductionmentioning
confidence: 99%